Bis-Schiff bases of isatin as new and environmentally benign corrosion inhibitor for mild steel - Ansari K.R.; Quraishi M.A. (My University, 2025)
Inhibition effect of three bis-Schiff bases of isatin namely (2-methoxybenzylidene) hydrazono) indolin-2-one (HZ-1), (2-hydroxybenzylidene) hydrazono) indolin-2-one (HZ-2) and (4-nitrobenzylidene) hydrazono) indolin-2-one (HZ-3) was studied on mild steel corrosion in 1.0M HCl by gravimetric measurements, electrochemical impedance spectroscopy (EIS), potentiodynamic polarization and quantum chemical study. The values of activation energy (Ea), equilibrium constant (Kads), free energy of adsorption δG°ads, activation enthalpy δH* and activation entropy δS*were discussed. The adsorption of inhibitors on metal followed Langmuir's adsorption isotherm. SEM and EDX observations confirmed the existence of protective inhibitor film on metal surface. Quantum chemical study supports the comparative inhibition effect of HZs. © 2013 The Korean Society of Industrial and Engineering Chemistry.